PERANCANGAN ALAT PENDETEKSI PENCURIAN DAN PELACAK SEPEDA MOTOR BERBASIS WIFI MENGGUNAKAN NODEMCU ESP8266 - Nasrudin, Nasrudin; Endi Permata; Didik Aribowo (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2025)
Motorcycle theft is a common criminal act in society. Therefore, a vehicle security system is needed that can provide a fast response and real-time location information. This research aims to design and implement a theft detection and tracking system for motorcycles based on the WIFI using NodeMcu ESP8266, SW- 420 vibration sensor, and GPS NEO-6M module, integrated with a web server interface for remote control and monitoring. The research uses hardware and software engineering methods, with a Waterfall approach. The research stages include literature studies, problem identification, system design, tool assembly, software development, system testing, and evaluation. The components used include ESP8266, SW-420 vibration sensor, NEO-6M GPS, and relay module. The system is designed so that when vibration is detected, an alarm is activated and a notification is sent via email. GPS will send the vehicle coordinates to the Web Server to be monitored by the user. Test results show that the system can respond to vibration disturbances within an average of 1 second, control the engine and starter relays within 1–3 seconds, and track the vehicle's location with an average accuracy of 8.33 meters and a tracking delay of approximately 50 seconds. The system was successfully accessed via smartphone hotspot with a maximum effective range of 15 meters. Therefore, this system is proven to be an effective, practical, and affordable IoT- based solution for motorcycle security that can be easily accessed by users through mobile devices.